Fodder Strategy for Sustainable Animal Production in Arid Rajasthan - Sharma, N K (Annals of Arid Zone, 2016)
Forage and feeds are the major inputs in animal husbandry, which constitute nearly 70% of the total cost of production. Cultivated fodders, including dual purpose crops, residue of field crops, rangelands and pastures, fodder trees and shrubs, etc. are multiple sources of fodder for animals in arid Rajasthan. For sustainable animal production, the improved cultivation and management practices of all these fodder resources along with fodder conservation and utilization strategy need to be developed in arid Rajasthan. Key words: Cultivated fodder crops, dual purpose crops, pasture grasses, trees and shrubs.